CGIAR Food Systems Accelerator Entrepreneur Spotlight: Forest Africa Zambia Ltd: Redefining Fruit Processing for a Greener Future - Zulu-Hume, Mercy F. (2023)
What if indigenous wild fruit processing could catalyse sustainable economic development, environmental conservation, and healthier food choices? Forest Africa Zambia Ltd, a Zambian company, is redefining the landscape by focusing on organic and healthy indigenous wild fruits. In a country where rural communities face challenges of limited livelihood options, and the impacts of climate change, Forest Africa Zambia Ltd is charting a new path. Specializing in processing organic indigenous wild fruit juices, they embrace a zero-waste philosophy that maximizes the potential of these wild fruits. Through their innovative business model and commitment to community empowerment, Forest Africa Zambia Ltd is not only addressing pressing environmental issues but also creating alternative livelihood opportunities for rural communities through Ecosystem-based Adaptation and healthier consumption choices for consumers.